HOSPEX in the antipodes. Issue 4 (15th December 2014) - Gill, Gerard; Butt, P; Reade, M C; Crozier, J; Williams, A; Thomas, T; Flint, B; Matthews, G; Duff, N; Brown, G; Chambers, A; Courtenay, B; et al.
Abstract : The Australian Army recently adopted the British concept of hospital exercise (HOSPEX) as a means of evaluating the capabilities of its deployable NATO Role 2E hospital, the 2nd General Health Battalion. The Australian approach to HOSPEX differs from the original UK model. This article describes the reasons why the Australian Army needed to adopt the HOSPEX concept, how it was adapted to suit local circumstances and how the concept may evolve to meet the needs of the wider Australian Defence Force and our allies.